The effects of handling on the quality changes of yellowfin tuna (Thunnus albacores) caught in Panay Gulf "Philippines" T. Eric M. Cooper. - Cooper, T. Eric M. (Miagao, Iloilo University of the Philippines Visayas, 2013)
Study on the effects of handling on the quality changes of Yellowfin tuna (Thunnus albacores) caught in Panay Gulf, Philippines was conducted by utilizing chilled seawater and crushed ice as the storage variables. Initially, determination of the chilling rate of tuna in chilled seawater and crushed ice found out that the former cooled the tune faster with lower temperature than latter did. Changes in sensory, chemical and microbial attributes were investigated thereafter for the period of 10 days and analyzed. Accordingly, the sensory attributes namely texture, color and odor for both storage media shown a significant deterioration with storage time (P.0.05) but did not go beyond the threshold of sensorial unacceptability (> 10 mean score) evaluated by the 10 panel members. The changes in the physic-chemical property of the tuna sample were observed through determination of % K-value, pH, indole, and histamine. The % K-value of the tuna samples significantly increased (P>0.05) with time in which the values had exceeded the sashimi grade limit of <20% however still deemed fresh in the <70% standard. The pH values interestingly were observed to be fluctuating over storage time. The concentration of indole had not reached the borderline safety for human consumption which is 65.50ug100g-1, while histamine concentration which considered as a crucial hazardous index for scombroid species of tuna samples did not exceed the USFDA Defect Action Level of 200ppm and the maximum level of 500ppm. Moreover, microbial load of the presence of coliform at a certain level was for human consumption in the period of 10 d storage. Positive correlation between indole and microbial load was revealed.
Thesis (M. S. Fisheries-Fish Processing Technology) -- Miagao, Iloilo : University of the Philippines Visayas, 2013.